RESPONSE OF MICROALGAE IN A CHANGING CLIMATE AND ENVIRONMENT - Wai-, Kuan Yong; Yong-, Hao Tan; Sze-, Wan Poong; Phaik-, Eem Lim (Malaysian Journal of Science, 2016)
Microalgae are ecologically important as a major primary productivity driver via photosynthetic carbon fixation. As the primary producers and food sources for higher trophic organisms, microalgae play a crucial role in maintaining the equilibrium of food webs in the aquatic ecosystem. The current shifts of global climate due to anthropogenic release of greenhouse gases have been reported to pose numerous impacts on microalgae. Extreme fluctuations in atmospheric temperature, light intensity, ultraviolet (UV) radiations, carbon dioxide (CO2) levels, and salinity can lead to alterations in growth, disruption of homeostasis, photosynthetic rate, respiration, enzymatic activity, protection to oxidative damage, and trophic transfer in microalgae. Various studies on microalgal responses to these environmental changes are ongoing to provide a deeper insight into the relationship between microalgal growth, metabolic adjustment and community structure. In this review the authors aim to highlight the recent findings on the responses of microalgae in the changing environment. Keywords: microalgae, climate change, environmental factors